Nature playscape for preeschoolers: what the parent says? - Abd Razak, Nurul Aqila; Ahmad Zawawi, Azita; Khairi, Nurfarhana (Faculty of Forestry and Environment Universiti Putra Malaysia, 2023)
The outdoor recreation space or nature playscape is one of the settings where preschoolers can enjoy nature, play and explore the world. However, in Malaysia, research on learning with nature still needs to be explored, explicitly concerning parents’ perspectives, who will choose what is best for their child in terms of space setting for nature play. Most research on the educational system emphasises structured learning and more studies are needed to explore the importance of setting and nature play. This preliminary study examines the parents’ view on preschoolers’ play behaviour with the needs of nature playscape. A cross-sectional online survey-based study was conducted on Malaysian parents (n=100) of children between ages 3 and 6 (preschoolers). This study found that preschoolers’ connection with nature and play in natural playscapes can offer various affordances, including building resilience (68%), promoting physical development (66%), and creating opportunities for discovery (66%). However, the need for supervision and the lack of natural space are the main barriers to outdoor nature play for preschoolers. The study recommends further research to examine the potential of outdoor recreation space features for preschoolers’ nature play development and enhancement, to provide more diverse and quality outdoor recreation spaces to support preschoolers’ healthy development across the spectrum.